2017
DOI: 10.1093/jcr/ucx093
|View full text |Cite
|
Sign up to set email alerts
|

Happy Wife, Happy Life: Food Choices in Romantic Relationships

Abstract: The authors extend research on dyadic decision making by examining how relationship partners influence consumer eating patterns. Using research from relationship science and evolutionary psychology, the authors find that romantic relationship motives of formation and maintenance influence eating behaviors. Specifically, females are influenced by the eating patterns (i.e., healthiness/unhealthiness) of males when relationship formation motives are active, while males are influenced by the eating patterns of fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…Table 1 presents the distribution of the observations retrieved in terms of the number of commensals composing each table. Note that almost 60% of the tables (n = 124) are composed by two persons or couples, which relates our findings complementarily to the study undertaken by Hasford et al (2018) who analyzed the influence of relationship partners on consumer eating patterns. They found that when relationships are forming, females tend to be influenced by the eating patterns of males, while the opposite effect arises when partners aim at maintaining their relationships.…”
Section: Data Descriptionsupporting
confidence: 74%
See 1 more Smart Citation
“…Table 1 presents the distribution of the observations retrieved in terms of the number of commensals composing each table. Note that almost 60% of the tables (n = 124) are composed by two persons or couples, which relates our findings complementarily to the study undertaken by Hasford et al (2018) who analyzed the influence of relationship partners on consumer eating patterns. They found that when relationships are forming, females tend to be influenced by the eating patterns of males, while the opposite effect arises when partners aim at maintaining their relationships.…”
Section: Data Descriptionsupporting
confidence: 74%
“…They found that when relationships are forming, females tend to be influenced by the eating patterns of males, while the opposite effect arises when partners aim at maintaining their relationships. Thus, a potential benchmark follows from the results obtained by Hasford et al (2018), even though we have no information on the relationship status of commensals given the nature of our data collection.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Once feelings of connection with a social presence are established, close others can affect consumers’ information sharing behaviors (e.g., Chen, ; Huang et al, ) and product preferences (Goode, Hart, & Thomson, ; Hasford, Kidwell, & Lopez‐Kidwell, ; Huang, Dong, & Zhang, ). Moreover, because jeopardizing an existing social connection is undesirable, consumers are often motivated to protect both valued relationships (e.g., Umashankar et al, ) and their partner (e.g., Dubois, Bonezzi, & De Angelis, ).…”
Section: Three Types Of Social Influencementioning
confidence: 99%
“…Gender effects are accounted for only when considering romantic relationships. In this regard, Hasford, Kidwell, and Lopez-Kidwell (2018) examined how the formation and maintenance of romantic relationships influenced the eating behavior of partners, an effect that differs considerably between genders.…”
Section: Literature Reviewmentioning
confidence: 99%